Impact of a Swept Source-Optical Coherence Tomography Device on Efficiency in Cataract Evaluation and Surgery: A Time-and-Motion Study - Multack S; Pan LC; Timmons SK; Datar M; Hsiao CW; Babu R; Pan SM; Woodard L (Clinical Ophthalmology, 2023)
Samuel Multack,1 Li-Chen Pan,2 Sean K Timmons,2 Manasi Datar,2 Chia-Wen Hsiao,3 Raiju Babu,3 Sun-Ming Pan,3 Lawrence Woodard4 1Multack Eye Care and Associates, Olympia Fields, IL, USA; 2Commercial Strategy and Market Access, Boston Healthcare Associates (a Veranex Company), Boston, MA, USA; 3Health Economics and Outcomes Research, Alcon, Fort Worth, TX, USA; 4Atlanta Eye Surgery Center, Atlanta, GA, USACorrespondence: Samuel Multack, Multack Eye Care and Associates, 20303 Crawford Ave, Olympia Fields, IL, 60461, USA, Tel +1-708-898-1858, Email smultack@mecvision.comPurpose: This study aims to assess the time impact of ARGOS® (image-guided swept-source optical coherence tomography biometer integrated with operating room (OR) technologies (SS-OCT w/ORT)) compared to LENSTAR LS 900 (optical low-coherence reflectometry (OLCR)), IOLMaster 500 (partial coherence interferometry (PCI)), and IOLMaster 700 (SS-OCT) on efficiency in the cataract evaluation and surgery.Patients and Methods: Data from 212 patients (two study sites) who underwent evaluation and/or cataract surgery were collected. The primary objective was to compare the performance of four biometers; statistical analyses were conducted to compare 1) biometer measurement times for all patients (ANOVA w/post-hoc Dunnett’s test) and stratified by cataract density (ANOVA) and 2) rate of biometer acquisition failure (Chi-square test w/post-hoc Bonferroni correction). Real-world observational data collected were then used to develop a practice-based time-efficiency model to demonstrate the combined effect that adopting an SS-OCT w/ORT has on a practice’s cataract workflow. Real-world data inputs included assessment of patient’s eyes’ cataract grade density, time taken for optical biometry, Manual A-scan (ultrasound biometer) when acquisition failed, and measurement times associated with other devices used in cataract evaluation and surgery.Results: For 208 patients (56% non-dense, 44% dense), the SS-OCT w/ORT biometer had a 0% acquisition failure (SS-OCT: 3% (p = 0.05); OLCR: 5% (p = 0.004); PCI: 15% (p < 0.0001)) and an average time savings of 30 seconds/patient compared to the other biometers in this study (p < 0.05). When acquisition failed, ultrasound biometry resulted in an additional 2.5 minutes/patient. For a cohort of 1000 patients, an SS-OCT w/ORT and an image-guidance system adopted at a practice using an SS-OCT, femtosecond laser, and intraoperative aberrometer offer up to 58% efficiency gain across the cataract workflow.Conclusion: Results from this study demonstrate an SS-OCT w/ORT’s efficiencies in cataract evaluation and surgery driven by faster measurement times, reducing the need for ultrasound biometry, and its integration benefits with other devices.Keywords: cataract surgery, swept-source optical coherence tomography biometer, time-and-motion study, preoperative evaluation phase